Auxin Contributes to the Intraorgan Regulation of Gene Expression in Response to Shade. Issue 2 (4th May 2018) - Kim, Sujung; Mochizuki, Nobuyoshi; Deguchi, Ayumi; Nagano, Atsushi J.; Suzuki, Tomomi; Nagatani, Akira
Abstract : Many genes are preferentially up-regulated by shade stimulus in the vasculature of Arabidopsis thaliana cotyledons, some of which are regulated by newly synthesized auxin in the mesophyll and/or epidermis. Abstract: Plants sense and respond to light via multiple photoreceptors including phytochrome. The decreased ratio of red to far-red light that occurs under a canopy triggers shade-avoidance responses, which allow plants to compete with neighboring plants. The leaf acts as a photoperceptive organ in this response. In this study, we investigated how the shade stimulus is spatially processed within the cotyledon. We performed transcriptome analysis on microtissue samples collected from vascular and nonvascular regions of Arabidopsis ( Arabidopsis thaliana ) cotyledons. In addition, we mechanically isolated and analyzed the vascular tissue. More genes were up-regulated by the shade stimulus in vascular tissues than in mesophyll and epidermal tissues. The genes up-regulated in the vasculature were functionally divergent and included many auxin-responsive genes, suggesting that various physiological/developmental processes might be controlled by shade stimulus in the vasculature. We then investigated the spatial regulation of these genes in the vascular tissues. A small vascular region within a cotyledon was irradiated with far-red light, and the response was compared with that when the whole seedling was irradiated with far-red light. Most of the auxin-responsive genes were not fully induced by the local irradiation, suggesting that perception of the shade stimulus requires that a wider area be exposed to far-red light or that a certain position in the mesophyll and epidermis of the cotyledon be irradiated. This result was consistent with a previous report that auxin synthesis genes are up-regulated in the periphery of the cotyledon. Hence, auxin acts as an important intraorgan signaling factor that controls the vascular shade response within the cotyledon.